Pengaruh Pemberian Kompres Hangat Jahe Merah Terhadap Nyeri Pada Pasien Osteoarthritis - Bitcar, Bitcar; Idris, Syamsul (Universitas Haji Sumatera Utara, 2025)
Osteoarthritis is a public health problem that is currently increasing, and is the main cause of musculoskeletal pain. Joint pain is the most common complaint, localized pain and pain will increase if there is movement in the affected joint, pain can also spread and will interfere with the patient's physical mobility. The role of nurses is very important in minimizing complaints due to the disease. One of the therapies carried out by nurses in cases of osteoarthritis is by providing warm compresses using red ginger. The purpose of this study was to determine the effect of providing warm compresses with red ginger on pain in osteoarthritis patients. This study was conducted at Rantauprapat Hospital from August to October 2024, using a quantitative research type and a quasi-experimental research approach, pretest posttest design. The study population was patients with osteoarthritis who were hospitalized with an average of 78 people each month. The sample in this study was 35 people with a sampling technique using purposive sampling. The measurement of the pain scale was carried out with an observation sheet using a numeric rating scale with a scale of 1-10. Data analysis in this study used the paired t test. The results of the study showed that the pain scale of respondents before the red ginger warm compress therapy with an average / mean of 3.57. The pain scale of respondents after the red ginger warm compress was given an average / mean of 2.77. The results of the paired t test with a sig. value of 0.000. The conclusion of the study showed that there was a significant effect of giving red ginger warm compresses on pain in osteoarthritis patients. It is recommended that patient families and health workers can make red ginger warm compresses one of the alternative actions in reducing the pain scale in patients with pain problems due to osteoarthritis.